2015
DOI: 10.1186/s12974-015-0459-5
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent adult progenitor cells for hypoxic-ischemic injury in the preterm brain

Abstract: BackgroundPreterm infants are at risk for hypoxic-ischemic encephalopathy. No therapy exists to treat this brain injury and subsequent long-term sequelae. We have previously shown in a well-established pre-clinical model of global hypoxia-ischemia (HI) that mesenchymal stem cells are a promising candidate for the treatment of hypoxic-ischemic brain injury. In the current study, we investigated the neuroprotective capacity of multipotent adult progenitor cells (MAPC®), which are adherent bone marrow-derived cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 46 publications
8
33
0
Order By: Relevance
“…Enrollment into a double‐blind, placebo controlled clinical trial of MAPC, for the treatment of ischemic stroke has recently been completed . Prior studies have demonstrated that MAPC are not immunogenic and have the capacity to exert potent immunomodulatory effects ; however, the impact of MAPC modulating splenic activation and immune responses after ischemic stroke remain largely unknown. In the present study, using a clinically relevant rat surgical model of focal ischemic stroke, we performed tissue microarray analyses to query the impact of ischemic injury and MAPC treatment upon gene expression and identified significant ischemia‐induced enrichment of genes related to inflammation and immune responses that were suppressed in animals treated with MAPC.…”
Section: Introductionmentioning
confidence: 99%
“…Enrollment into a double‐blind, placebo controlled clinical trial of MAPC, for the treatment of ischemic stroke has recently been completed . Prior studies have demonstrated that MAPC are not immunogenic and have the capacity to exert potent immunomodulatory effects ; however, the impact of MAPC modulating splenic activation and immune responses after ischemic stroke remain largely unknown. In the present study, using a clinically relevant rat surgical model of focal ischemic stroke, we performed tissue microarray analyses to query the impact of ischemic injury and MAPC treatment upon gene expression and identified significant ischemia‐induced enrichment of genes related to inflammation and immune responses that were suppressed in animals treated with MAPC.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β expression was increased in blood up to 24 h after exposure to repetitive umbilical cord occlusions and microglia counts were increased in the white matter and hippocampus at 24 h [ 55 ]. Other studies also demonstrated the central activation of microglia associated with systemic inflammation and the influx of neutrophils into the brain after 25 min of umbilical cord occlusion in fetal sheep [ 56 , 57 , 58 , 59 ].…”
Section: Inflammation Associated With Ischemic-reperfusion Injury mentioning
confidence: 96%
“…In preterm fetal sheep, global HI caused a potent neuroinflammatory response, characterized by excessive microglial activation, from 3 h [ 59 ] until 21 days post-HI [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. This was associated with acute loss of pre-OLs at 72 h after the insult, and restoration of pre-OL numbers at seven days and 14 days post-reperfusion, in association with the increased restorative proliferation of oligodendrocyte progenitors [ 63 , 74 , 75 ].…”
Section: Preterm Brain Injury—timing Is Keymentioning
confidence: 99%